Effectiveness of Laser Therapy in the Management of Recurrent Aphthous Stomatitis: A Systematic Review - Min Han; Hui Fang; Quan-Li Li; Ying Cao; Rong Xia; Zhi-Hong Zhang (Scientifica)
Objectives. Laser therapy is a promising new treatment for patients with recurrent aphthous stomatitis (RAS). However, the clinical effect and security issue of laser therapy remain controversial. This systematic review was conducted to evaluate the clinical effectiveness and security of laser treatment in RAS patients. Methods. Five electronic databases were searched (MEDLINE (PubMed), EMBASE, ScienceDirect, the Cochrane Library, and Web of Science) to identify all studies that were about randomized controlled clinical trials, involving the effect of laser therapy in RAS patients. Conclusion. Twenty-three studies were retained for full-text analysis after screening the titles and abstracts of potential articles, but only 10 studies satisfied the inclusion criteria after the full texts were reviewed. The included studies reported a comparison of the effectiveness between the laser treatment and placebo laser therapy (or conventional drug therapy) when managing the RAS patients. It can be concluded that laser therapy has the superiority in relieving ulcer pain and shortening healing time when compared with placebo group or medical treatment group. Although laser therapy is a promising effective treatment for RAS, high-quality clinical studies with large sample size must be further performed to confirm the effectiveness of this therapy.